2022
DOI: 10.3390/ijms232012347
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of circRNA Expression throughout the Light-Dark Cycle Reveal a Strong Regulation of Cdr1as, Associated with Light Entrainment in the SCN

Abstract: Circular RNAs (circRNAs) are a large class of relatively stable RNA molecules that are highly expressed in animal brains. Many circRNAs have been associated with CNS disorders accompanied by an aberrant wake–sleep cycle. However, the regulation of circRNAs in brain homeostasis over daily light–dark (LD) cycles has not been characterized. Here, we aim to quantify the daily expression changes of circRNAs in physiological conditions in healthy adult animals. Using newly generated and public RNA-Seq data, we monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 89 publications
0
1
0
Order By: Relevance
“…Studies have demonstrated that circRNAs influence melatonin metabolism and circadian rhythm by sponging miRNAs in the pineal gland [20,56]. Cir-cRNA Cdr1as strongly regulates light entrainment during a 12:12 h light/dark cycle in the SCN tissue [21]. Here, we identified five circRNAs that are differentially expressed in light and dark conditions, and a network covering 15 circadian circRNA-mRNA pairs was constructed in accordance with the rhythmic pattern.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies have demonstrated that circRNAs influence melatonin metabolism and circadian rhythm by sponging miRNAs in the pineal gland [20,56]. Cir-cRNA Cdr1as strongly regulates light entrainment during a 12:12 h light/dark cycle in the SCN tissue [21]. Here, we identified five circRNAs that are differentially expressed in light and dark conditions, and a network covering 15 circadian circRNA-mRNA pairs was constructed in accordance with the rhythmic pattern.…”
Section: Discussionmentioning
confidence: 97%
“…Zheng et al reported that circ-WNK2 promotes elevated levels of the circadian gene AANAT by sponging miR-328a-3p in rat pineal gland tissue [20]. Ivanov et al proved that cir-cRNA Cdr1as is regulated during 12:12 h light/dark cycles in the SCN and affects the adaptation to daily changes [21]. Zhao et al found that the circadian gene BMAL1 could bind to the promoter of circGUCY1A2 and increases its expression in non-small cell lung cancer cases [22].…”
Section: Introductionmentioning
confidence: 99%
“…76 Moreover, the rhythmic expression of cdr1-AS in the suprachiasmatic nucleus (a central circadian pacemaker in the brain) has been observed which influences the rhythmicity of the brain by interacting with proteins regulating clock genes. 77 Another circular RNA, cirFoxo3, associates itself with a RNA binding protein ID2 (Inhibitor of DNA binding/differentiation protein). This, in turn, inhibits ID2 regulated proteosomal degradation of the key transcription factors involved in neuronal differentiation of the progenitor cells to different types of neurons and glial cells.…”
Section: Non-coding Rnas As Regulators In the Brain: Neuronal Develop...mentioning
confidence: 99%
“…Cdr1as KO mice were identified with behavioral abnormalities, namely, sensorimotor gating phenotype that is associated with neuropsychiatric disorders and dampened neural activity in in vitro autaptic neuronal cultures (Piwecka et al, 2017 ). However, the study by Ivanov et al, brings another layer of complexity to Cdr1as functions in neurons and circRNA stability, as it clearly implies that Cdr1as undergoes dynamic turn-over in the suprachiasmatic nucleus over the LD cycles (Ivanov et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%